Comparative analysis of combustion and emission characteristics in RCCI engines using alcohol fuels with different carbon numbers - Fırat, Müjdat; Okcu, Mutlu; Varol, Yasin; Altun, Şehmus (Springer, 2024)
Alcohol fuels with different carbon numbers such as propanol (C3), butanol (C4) and pentanol (C5) have lately become popular in both conventionally and RCCI-operated diesel engines thanks to their high cetane number (CN) and oxygen content along with lower latent heat of evaporation, which are useful for reducing the high CO/HC emissions, whereas RCCI mode still suffers from these emissions. Therefore, in this study, these three alcohol fuels with carbon numbers ranging from C3 to C5 were employed as low-reactivity fuel (LRF) in a single-cylinder RCCI engine under a constant engine speed of 2400 rpm and varying loadings (from 20 to 60% of full load at 20% intervals) and premixed ratios (from 0 to 60% with 15% intervals) when using B7 as high-reactivity fuel (HRF). In the experimental study, the effect of oxygen content, latent heat of evaporation, and cetane number which changes linearly with the carbon number of alcohols used, on exhaust emissions, were analyzed. When compared to conventional diesel mode (CDM), RCCI mode using alcohol fuels increased HC and CO emissions but decreased smoke opacity at a great level. The greatest reduction in both CO emissions and smoke opacity was recorded with the use of propanol which has the highest oxygen content, while pentanol with the lowest latent heat of evaporation had success in reducing HC emissions. In addition, NOx emissions were reduced by up to 60% when butanol was used as low-reactivity fuel. Ignition delay increased more during RCCI operation with propanol having an octane number of 118, whereas butanol and pentanol have 92 and 78, respectively. It was concluded that the properties of alcohol fuels such as the oxygen content and latent heat of evaporation had a significant effect on HC/CO emissions in RCCI engines. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.
Keywords: Diesel; Emissions; Low-temperature combustion; Lower alcohols; RCCI